Pembelajaran Komputasi dalam Arsitektur Tingkat Awal - Riva Tomasowa (Bina Nusantara University, 2011)
The architecture curriculum in formal education is necessary to be redefined in order to adapt to computing technology to obtain its good values. CAAD is added to architecture learning with no settled framework; relying on practical experience of lecturers. This reminds of how important the adaptation to the theories and science of architecture that evolved with the advent of digital media is. Therefore, the methodology and teaching approach systems are need to be reviewed, with the help of architects, professionals and the authority to fix the narrow perception of digital architecture. This article is a summary of several earlier studies on the influence of information technology on the education of architecture lately. It is expected that in the future this article may be useful as a theoretical basis for the course Computational Design in Architecture Architecture I at Bina Nusantara University.